(untitled) (European Journal of Pure and Applied Mathematics, 2022)
The purpose of this work is to introduce and study a new topological property called epi-complete-regularity. A space (X, T ) is called an epi-completely-regular space if there exists a topology T′ on X which is coarser than T such that (X, T′) is Tychonoff. This new property is investigated and some examples are presented in this work to illustrate its relationships with other kinds of normality and complete-regularity.